Preventive measures for dental erosion - Ionta, Franciny Querobim (2018)
In recent years, due to the high prevalence of dental erosion, therapies to prevent the occurrence or inhibit the progression of this condition have been searched. The purpose of this thesis was to present four articles that evaluated possible preventive measures for enamel erosion. Specifically, it was evaluated: article I - the effect of five types of vegetable oils against initial enamel erosion; article II - protective effect of palm oil alone or associated with a fluoride solution against erosive enamel wear (chemicalmechanical/ toothbrushing); article III - the protective potential against erosive tooth wear of an aspartame solution, used as mouthwash prior to acid exposure; article IV - the effectiveness of a dentifrice with calcium silicate, phosphate and fluoride on the prevention of erosive wear (chemical-mechanical/toothbrushing). In all articles, deionized water (DW) was used as negative control and a solution (SS) or dentifrice (SD) containing fluoride and stannous as positive control. The response variable adopted was loss of surface hardness for article I and enamel loss in height for articles II, III and IV. In article I, two volunteers used the intraoral appliance for 2 hours to form the acquired pellicle and then the enamel blocks of each study group were treated in vitro by 5 different vegetable oils at 2 different concentrations (5 or 100%). Then, the blocks were immersed in artificial saliva for 2 minutes and subjected to 0.5% citric acid for 2 minutes. Data were analyzed by one-way ANOVA and Tukey\'s test (p <0.05). Among the evaluated vegetable oils, palm oil was the only one that presented protective potential against initial enamel erosion, resulting in less hardness loss than DW and SS. In Article II, volunteers used intraoral appliances in situ for 5 days, in which 4 ex vivo erosive cycling with 0.5% citric acid for 2 minutes was carried out. Prior to the first and third erosive challenge, DW, SS and palm oil associated or not to SS were applied on enamel blocks by administration of one drop of the respective solution, followed by acid immersion. Then, the abrasive challenge was performed (brushing for 15 seconds). Data were submitted to 2-way ANOVA and Tukey\'s test (p <0.05). For both, erosion and erosion + abrasion, palm oil alone or associated to SS resulted in less enamel loss than DW, but did not differ from SS. In article III, 4x/day volunteers performed in situ mouthwashes with DW, SS or 0.024% aspartame solution. Then half enamel blocks were immersed ex vivo in intrinsic (0.01M hydrochloric acid pH 2.3) and the other half in extrinsic (0.03 citric acid pH 2.4 for 2 minutes) acid challenge for 5 days. After statistical analysis (2-way ANOVA and Tukey\'s test, p <0.05), it was observed that aspartame was similar to DW and resulted in greater loss of enamel than SS. Hydrochloric acid promoted higher enamel loss than citric acid. In article IV, volunteers used intraoral appliances in situ for 5 days and 4 erosive cycling with 0.5% citric acid for 2 minutes was carried out. Right after the first and third cycling of the day the dentifrices, including the one with addition of calcium silicate, phosphate and fluoride, were applied for 1 minute and then, half of the enamel specimens were brushed for 15 seconds (abrasion). Statistical analysis was performed by 2-way ANOVA and Fischer\'s exact test (p <0.05). The dentifrice containing calcium silicate, sodium phosphate and fluoride protected the enamel against erosion similar to SD; but when subjected to abrasion by brushing, it showed similar enamel loss than DW, demonstrating no protective effect. Among the tested preventive measures, palm oil presented promising results in the prevention of erosive tooth wear, similarly to a stannous-solution. Aspartame, however, did not present a preventive effect against erosive tooth wear caused by intrinsic or extrinsic acid. The dentifrice containing calcium silicate, sodium phosphate and fluoride only presented a preventive effect against erosion but it did not show a protective effect against erosive tooth wear.